Label-free quantitative analysis of lipid metabolism in living Caenorhabditis elegans[S] - Thuc T. Le; Holli M. Duren; Mikhail N. Slipchenko; Chang-Deng Hu; Ji-Xin Cheng (Journal of Lipid Research, 2010)
The ubiquity of lipids in biological structures and functions suggests that lipid metabolisms are highly regulated. However, current invasive techniques for lipid studies prevent characterization of the dynamic interactions between various lipid metabolism pathways. Here, we describe a noninvasive approach to study lipid metabolisms using a multifunctional coherent anti-Stokes Raman scattering (CARS) microscope. Using living Caenorhabditis elegans as a model organism, we report label-free visualization of coexisting neutral and autofluorescent lipid species. We find that the relative expression level of neutral and autofluorescent lipid species can be used to assay the genotype-phenotype relationship of mutant C. elegans with deletions in the genes encoding lipid synthesis transcription factors, LDL receptors, transforming growth factor β receptors, lipid desaturation enzymes, and antioxidant enzymes. Furthermore, by coupling CARS with fingerprint confocal Raman analysis, we analyze the unsaturation level of lipids in wild-type and mutant C. elegans. Our study shows that complex genotype-phenotype relationships between lipid storage, peroxidation, and desaturation can be rapidly and quantitatively analyzed in a single living C. elegans.